Strategi Penerapan Pendidikan Islam Di Madrasah Dan Di Sekolah - Cut Dewi Rahma; Miftahul Jannah (LPPM STAI La Tansa Mashiro, 2025)
Educational strategies are plans or patterns of action designed to achieve learning objectives effectively and efficiently so as to increase student motivation and learning outcomes. The strategy of implementing Islamic education in madrasahs and schools faces various challenges, such as differences in curriculum, limited resources, and lack of integration of Islamic values in learning activities. This research focuses on assessing effective Islamic education implementation strategies by examining various important aspects, such as curriculum development, learning methods, teacher competence, technology utilization, and the role of parents in supporting the education process. The research method used is a literature study by analyzing various sources, including scientific journals, books, and related documents. The results show that the strategies for effective implementation of Islamic education include comprehensive curriculum development, active and innovative learning approaches, improving the competence of Islamic education teachers, utilizing technology in learning, and strengthening the role of parents. With the implementation of these strategies, it is expected that Islamic education can have a significant positive impact on the development of students in madrasah and public schools.Keywords: Strategy, implementation, Islamic education, madrasah and schools